Hannā Diyāb’s “A Sultan of Samarcand”, an Eleventh-Century Old Georgian St. George Legend, and the Construction of an Early Modern Fairy Tale - B. Bottigheimer, Ruth (Ethnographica et Folkloristica Carpathica, 2021)
Of the sixteen stories Hannā Diyāb told Antoine Galland to help the elderly scholar complete his 12-volume Mille et Une Nuits (1704–1717) six were omitted. This article examines one of the six discarded tales, “A Sultan of Samarcand”. Rediscovered by Hermann Zotenberg in the late 1880s, translated soon thereafter into English by Richard Burton, it was contextualized historically as a product of Eastern Christian narrative tradition by Joseph Szövérffy in 1956 and categorized typologically by him within the Aarne–Thompson tale-type index, as it then existed. Kevin Tuite’s recent research and translation of an eleventh-century Georgian religious legend supports my hypothesis that the Christian St. George legend supplied the story’s core episode. The role of reference works is introduced inter alia to illuminate their role within knowledge creation in general and in the discontinuities of “A Sultan of Samarcand” research in particular.